(untitled) (International journal of artificial intelligence, 2025)
This article presents a comparative linguacultural analysis of nature representation in English and Uzbek. It examines how nature is expressed through artistic means in both languages and cultures, analyzing their semantic and stylistic features. Additionally, the unique use of metaphors, epithets, and other poetic elements in Uzbek and English literature is explored. The study investigates the linguacultural perspectives on nature in both languages, identifying similarities and differences.